The effect of Helicobacter pylori eradication on symptoms and gastric emptying in patients with nonulcer dyspepsia - Cansel TÜRKAY,; İrfan SOYKAN,; Metin KIR,; Ali ÖZDEN, (Turkish Journal of Gastroenterology, 2019)
-